Design and performance of the ARIADNE+ detector, bringing novel 3D optical dual-phase LArTPCs to the large scale - Martinez, Pablo Amedo; Deisting, Alexander; Gatti, Heriques Frandini; González-Díaz, Diego; Lowe, Adam John; Majumdar, Krishanu; Mavrokoridis, Konstantinos; Nessi, Marzio; Philippou, Barney; Pietropaolo, Francesco; Ravinthiran, Sudikshan; Resnati, Filippo; et al. (Frontiers in Detector Science and Technology, 2025)
The ARIADNE programme is focused on the development of a scalable optical readout system for use in future ktonne LAr neutrino experiments, providing high tracking capability and low energy thresholds. Following demonstration at the 1 tonne scale (ARIADNE detector), a 20 tonne experiment has been performed at the CERN Neutrino Platform (ARIADNE+) to test scalability for integration into colossal future experiments such as those planned within the DUNE programme. This paper details the design, construction and performance of a 2.3 × 2.3 m light readout plane (LRP), which contained the largest glass THGEM array ever constructed. Four Timepix3 cameras were mounted externally to image the secondary scintillation light produced within the THGEM holes; three cameras operated with a visible image intensifier, and one with a VUV sensitive intensifier coupled to a custom magnesium fluoride lens. The Timepix3 data are natively zero suppressed, and with the 1.6 ns timing resolution, straightforward 3D event reconstruction is possible. A gallery of reconstructed LAr interactions is presented. Energy resolution and calibration were determined using cosmic muons. The energy resolution was found to be approximately 11% for the presented dataset. An outlook on the next steps for this work is given.